ACUTE RETINAL DAMAGE AFTER USING A TOXIC PERFLUORO-OCTANE FOR VITREO-RETINAL SURGERY. Issue 6 (June 2017) - Pastor, J. Carlos; Coco, Rosa M.; Fernandez-Bueno, Ivan; Alonso-Alonso, Maria L.; Medina, Jesús; Sanz-Arranz, Aurelio; Rull, Fernando; Gayoso, Manuel J.; Dueñas, Antonio; Garcia-Gutierrez, Maria T.; Gonzalez-Buendia, Lucia; Delgado-Tirado, Santiago; et al.
Abstract : Purpose: To describe a series of retinal acute toxicity cases with severe visual loss after intraocular use of a toxic perfluoro-octane (PFO). The clinical presentation is described, and the likely causes are analyzed. New biological methods for testing safety of intraocular medical devices are proposed. Methods: Information regarding a series of eyes suffering acute severe events after intraocular use of a toxic PFO was analyzed. Four types of spectroscopy, nuclear magnetic resonance, and chromatography were used to identify the potential PFO contaminants. Cultures of human retinal pigment epithelial cells (ARPE-19) and porcine neuroretina were used to quantify the toxicity of the suspect PFO lots. Results: Of 117 cases of intraocular toxicity, 96 were considered clearly related to the use of PFO. Fifty-three cases had no light perception, and 97 had no measurable visual acuity. Retinal necrosis (n = 38) and vascular occlusion (n = 33) were the most characteristic findings. Two hydroxyl compounds, perfluorooctanoic acid and dodecafluoro-1-heptanol, and benzene derivatives were identified as the suspected toxic agents. While existing toxicity testing failed, we proposed new tests that demonstrated clear toxicity. Conclusion: Protocols to determine cytotoxicity of intraocular medical devices should be revised to assure safety. Acute toxic events should be reported to health authorities and scientific media. Abstract : Inadequate cytotoxicity testing accepted by European Union (EU) and International Organization for Standardization (ISO) standards for perfluoro-octane used in intraocular surgery resulted in 117 cases of acute intraocular toxicity and severe loss of visual function. Clinical findings and an alternative method to determine cytotoxicity are described.